Is exercise effective for the management of subacromial impingement syndrome and other soft tissue injuries of the shoulder? A systematic review by the Ontario Protocol for Traffic Injury Management (OPTIMa) Collaboration. Issue 5 (October 2015) - Abdulla, Sean Y.; Southerst, Danielle; Côté, Pierre; Shearer, Heather M.; Sutton, Deborah; Randhawa, Kristi; Varatharajan, Sharanya; Wong, Jessica J.; Yu, Hainan; Marchand, Andrée-Anne; Chrobak, Karen; Woitzik, Erin; et al.
Abstract Background Exercise is a key component of rehabilitation for soft tissue injuries of the shoulder; however its effectiveness remains unclear. Objective Determine the effectiveness of exercise for shoulder pain. Methods We searched seven databases from 1990 to 2015 for randomized controlled trials (RCTs), cohort and case control studies comparing exercise to other interventions for shoulder pain. We critically appraised eligible studies using the Scottish Intercollegiate Guidelines Network (SIGN) criteria. We synthesized findings from scientifically admissible studies using best-evidence synthesis methodology. Results We retrieved 4853 articles. Eleven RCTs were appraised and five had a low risk of bias. Four studies addressed subacromial impingement syndrome. One study addressed nonspecific shoulder pain. For variable duration subacromial impingement syndrome: 1) supervised strengthening leads to greater short-term improvement in pain and disability over wait listing; and 2) supervised and home-based strengthening and stretching leads to greater short-term improvement in pain and disability compared to no treatment. For persistent subacromial impingement syndrome: 1) supervised and home-based strengthening leads to similar outcomes as surgery; and 2) home-based heavy load eccentric training does not add benefits to home-based rotator cuff strengthening and physiotherapy. For variable duration low-grade nonspecific shoulder pain, supervised strengthening and stretching leads to similar short-term outcomes as corticosteroid injections or multimodal care. Conclusion The evidence suggests that supervised and home-based progressive shoulder strengthening and stretching are effective for the management of subacromial impingement syndrome. For low-grade nonspecific shoulder pain, supervised strengthening and stretching are equally effective to corticosteroid injections or multimodal care. Systematic review registration number CRD42013003928.